Características sociodemográficas de uma população que busca o teste rápido como diagnóstico inicial do HIV em uma unidade de pronto-atendimento - Fraporti, Celita (2015)
The objective of this study refers to the identification of the sociodemographic profile of the population of one Emergency Care Unit of the Metropolitan region of Porto Alegre that sought the rapid HIV test and Syphilis as the initial disease diagnosis. This is an investigation, with approach through issues related to personal patient data, exposure category, and results of rapid tests. Data were collected from 224 medical charts archived in an Emergency Unit of the Metropolitan region of Porto Alegre from January 2012 to October 2014.The archived forms were filled out by (the) nurses (the) of one Emergency Care Unit the time of application of the rapid HIV test, as well as offering the rapid test Syphilis. The results were analyzed using SPSS 20.0 software. From the study population 54% are male, and 46% female. Regarding schooling 58.9% of patients who applied rapid test reported having completed elementary school. Regarding the results of the tests, 8.9% tests showed a positive result for HIV and 12.5% had reagent test for syphilis. The comparison among exposure categories and age groups of users, presented statistical relevance by the chi-square test (p <0.001). It is noteworthy that the comparison related to the rapid test for syphilis with sex had significant difference (p=0.004).It is concluded that the male tends to search the rapid test for HIV in one Emergency Care unit. From this it becomes necessary, planning and public health strategies aimed at this population profile.